The Effect of Students' Learning Activities and Creativity on The Learning Outcomes in The Aerodynamics - Tri Adi Prasetya; Chrisna Tri Harjanto; Angga Debby Frayudha (Jurnal Dinamika Vokasional Teknik Mesin, 2021)
Vocational education aims to prepare students to acquire knowledge and skills as provisions for work. The involvement of all aspects of students, both physical and spiritual, is needed to achieve the learning objectives. It shows that each student must be actively involved in the learning process. Creativity is an essential component of learning and problem-solving. Creative learning is related to cognitive development and the process of discovering and creating something new. This research was conducted to determine the effect of student learning activities and student creativity on learning achievement, both independently and simultaneously. The subjects of this study were students of class XI AP2 SMK Bina Dhirgantara Karanganyar. The data collection technique used tests and observations. Data analysis techniques used simple regression for the first and second hypotheses (independent effect) and multiple regression analyses for the third hypothesis (simultaneous effect). The results showed that student learning activities significantly affect learning achievement with a value of t arithmetic of 3.909, a higher value than the t table of 1.69. Student creativity significantly affects learning achievement, with the t arithmetic value of 4.281, higher than the t table of 1.69. The multiple regression analysis results showed that the coefficient of determination X1 and X2 against Y was 0.477 or 47.7%. It shows that the variables of student learning activities and student creativity have a contributing influence on learning achievement.